Sistem Pendukung Keputusan Pemberian Kredit Nasabah BPR Guguk Mas Makmur - Syahputra, Ronaldo; Nozomi, Irohito; Junaidi, Ahmad (PT. Riset Press International, 2024)
One of the services provided by BPR Guguk Mas Makmur is providing credit to customers. The process of granting credit is carried out through various considerations and conditions that must be fulfilled by the customer, then the Bank considers whether the customer is worthy of taking credit or not. The process of granting credit at the BPR Guguk Mas Makmur branch takes a long time because it is still done manually, so customers often move to other financing companies. This excessively long time is caused by an inaccurate analysis process, so the assessment process must be repeated. This is considered very inefficient and ineffective. Therefore, it is necessary to create a decision support system for credit eligibility at BPR Guguk Mas Makmur.